The sartorial man a case study on the identity construction of male fashion blog readers - Gancayco, Alessandra Loren Perez 1991- (2014)
"This study explored fashion blogger, David Guison's influence on his readers. It attempted to analyze the readers' image of self-identity and its relation to their level of fandom. The research framework was an integration of Sandvoss's theory on Fandom as extension of the self, Fiske's theory on Fan Productivity and Hall's Reception Theory. The researcher made use of a quantitative and qualitative research methods. By using the quantitative method, the researcher conducted a survey among 201 of Guison's readers. From this sample, 13 avid readers were chosen to participate in the personal interviews of the research. The researcher looked into the exposure, knowledge, level of intensity and fan productivity of the respondents in relation to Guison's blog in both the survey and interview methods. Through the study, the researcher discovered that: Guisons readers were moderately and highly knowledgeable regarding his personal and online life. Second, Guison's readers were able to connect with him easily because of his unique charm and humor that are exhibited on his blog. Next, Guison's style greatly influences his readers. However, most of them already integrated their own personal style into the outfits inspired by Guison. The manner in which they presented themselves had affected their optimism in different facets of life aside from just dressing up. Lastly, the greatest influence of Guison on his readers is his ability to push forward heir self-confidence through the way they present themselves to society. Guison serves as a motivation and inspiration to be true to oneself. Many of his readers had taken the extra step by sharing their own personal views on life by creating their own blogs as well."